Intermittent training: The benefits in football - Russo, E.; Russo, G.; Signorini, G.; Esposito, G. (Journal of Human Sport & Exercise, 2021)
The aim of this study is to verify the effectiveness of an intermittent training methodology in groups of boys belonging to the "Giovanissimi" category of 9-a-side football. The sample is made up of 10 athletes aged 14-15. The sporting season was divided following phases, that is, starting from a preparatory phase and then arriving at the competitive phase, the agonistic one. For the evaluation of the qualitative and quantitative data, each athlete was subjected to anthropometric tests (height, weight, BMI) and spinal flexibility tests both at entry and exit; for the evaluation of endurance, strength, speed, speed and agility the following tests were used: yo-yo Test, Sargent test, T-Test Agility, M test (20m adapted), Speed test 5m, 10m and 20mThrough the statistical model of the t-test for dependent samples, the effectiveness of the method used is evident. The data reveals significant increases for yo-yo Test, Sargent test, M (20m) test, T-Test agility. For the other tests carried out at the exit, there are no significant increases, because they are short-distance tests that show little increase, as the rapidity and speed, in this period of the developmental age, do not produce improvements for the morpho-functional adaptations specific. It has been shown how young boys, sedentary or moderately trained, can obtain benefits thanks to the proposed training, following an adequate programming and planning of training sessions according to their needs.